2010
DOI: 10.1590/s1677-55382010000100008
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic efficacy and safety of nonsteroidal anti-inflammatory drugs after transurethral resection of prostate

Abstract: Objectives: The aim of this study was to assess the analgesic efficacy and safety of nonsteroidal anti-inflammatory drugs (NSAIDs), administered as intramuscular diclofenac in comparison with intravenous paracetamol after transurethral resection of the prostate (TURP). Materials and Methods: Fifty men, aged 55 to 75 years, undergoing TURP at our hospital were included in this study. Patients were divided randomly and prospectively into two groups (25 patients in each group). Group I (NSAID) received 75 mg of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 18 publications
0
10
0
5
Order By: Relevance
“…(3) Nyeri pasca operasi TURP disebabkan karena trauma (reseksi jaringan prostat), iritasi foley kateter dan traksi kateter pasca TURP pada luka operasi. (4,5,6) Kara C et al Februari 2010 membandingkan efektifitas pemakaian Non Steroid Anti Inflamasi Drugs (NSAID) injeksi diklofenak dengan parasetamol drip. Kara C et all mendapatkan rata-rata nilai VAS pada kedua kelompok adalah > 3 cm pada 30 menit sampai 4 jam pertama pasca TURP Tetapi 6 jam berikutnya Artikel Penelitian terjadi peningkatan yang signifikan pada parasetamol dibandingkan dengan diklofenak.. (6) Pemakaian parasetamol oral dan tramadol oral sebagai analgetik pasca operasi sangat banyak bahkan termasuk salah satu analgetik yang direkomendasikan dalam guidelines manajemen nyeri pasca TURP oleh European Association of Urology.…”
Section: Pendahuluanunclassified
“…(3) Nyeri pasca operasi TURP disebabkan karena trauma (reseksi jaringan prostat), iritasi foley kateter dan traksi kateter pasca TURP pada luka operasi. (4,5,6) Kara C et al Februari 2010 membandingkan efektifitas pemakaian Non Steroid Anti Inflamasi Drugs (NSAID) injeksi diklofenak dengan parasetamol drip. Kara C et all mendapatkan rata-rata nilai VAS pada kedua kelompok adalah > 3 cm pada 30 menit sampai 4 jam pertama pasca TURP Tetapi 6 jam berikutnya Artikel Penelitian terjadi peningkatan yang signifikan pada parasetamol dibandingkan dengan diklofenak.. (6) Pemakaian parasetamol oral dan tramadol oral sebagai analgetik pasca operasi sangat banyak bahkan termasuk salah satu analgetik yang direkomendasikan dalam guidelines manajemen nyeri pasca TURP oleh European Association of Urology.…”
Section: Pendahuluanunclassified
“…Similarly, a study in patients undergoing transurethral prostate resection reported no added bleeding risk with the use of intramuscular diclofenac versus IV paracetamol [62]. It is important to note, however, that higher postoperative blood loss has been reported with administration of diclofenac versus placebo following breast surgery [63].…”
Section: Discussionmentioning
confidence: 99%
“…Effective postoperative pain management is an important concern for anesthesiologist and surgeon [10]. Approximately 80% of patients undergoing surgical procedures experience mild to severe post-operative pain, despite the major improvements in the understanding of post-operative pain pathology [9].…”
Section: Discussionmentioning
confidence: 99%